Donor treatment with a PHD-inhibitor activating HIFs prevents graft injury and prolongs survival in an allogenic kidney transplant model - Bernhardt, W. M.; Gottmann, U.; Doyon, F.; Buchholz, Björn; Campean, Valentina; Schödel, Johannes; Reisenbuechler, A.; Klaus, S.; Arend, M.; Flippin, L.; Willam, Carsten; Yard, B.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2009)
Long-term survival of renal allografts depends on the chronic immune response and is probably influenced by the initial injury caused by ischemia and reperfusion. Hypoxia-inducible transcription factors (HIFs) are essential for adaptation to low oxygen. Normoxic inactivation of HIFs is regulated by oxygen-dependent hydroxylation of specific prolyl-residues by prolyl-hydroxylases (PHDs). Pharmacological inhibition of PHDs results in HIF accumulation with subsequent activation of tissue-protective genes. We examined the effect of donor treatment with a specific PHD inhibitor (FG-4497) on graft function in the Fisher-Lewis rat model of allogenic kidney transplantation (KTx). Orthotopic transplantation of the left donor kidney was performed after 24 h of cold storage. The right kidney was removed at the time of KTx (acute model) or at day 10 (chronic model). Donor animals received a single dose of FG-4497 (40 mg/kg i.v.) or vehicle 6 h before donor nephrectomy. Recipients were followed up for 10 days (acute model) or 24 weeks (chronic model). Donor preconditioning with FG-4497 resulted in HIF accumulation and induction of HIF target genes, which persisted beyond cold storage. It reduced acute renal injury (serum creatinine at day 10: 0.66 +/- 0.20 vs. 1.49 +/- 1.36 mg/dL; P < 0.05) and early mortality in the acute model and improved long-term survival of recipient animals in the chronic model (mortality at 24 weeks: 3 of 16 vs. 7 of 13 vehicle-treated animals; P < 0.05). In conclusion, pretreatment of organ donors with FG-4497 improves short-and long-term outcomes after allogenic KTx. Inhibition of PHDs appears to be an attractive strategy for organ preservation that deserves clinical evaluation.
Keywords: hypoxia-inducible transcription factors; kidney injury; protection; transplantation